Опис використання сучасних методів розробки ігор на базі сучасного ігрового рушія Unreal Engine 5 - Турчин, А. А. (ХНУРЕ, 2023)
Ukrainian game development in the realities of wartime Ukraine received a rather strong push from the government, which allowed it to develop very quickly. The "Rise of Universe" project is designed both for a young audience, which is interested in graphics and new mechanics, and for an older audience, playing on their nostalgic feelings and immersing them in that atmosphere. The development will use the most modern and versatile game engine "Unreal Engine 5" at the moment, which will allow you to use the most advanced mechanics and particle processing systems to create the atmosphere of being in outer space, passing through various nebulae and gas anomalies.
Keywords: розробка ігор